A20 mRNA therapeutics ameliorate systemic sclerosis by suppressing TRAF-6/NF-KB signaling and DREAM expression and exerting antifibrotic effects - Lee, A Ram; Jeon, Su Been; Kwak, Hye Won; Yang, Suh Won; Bang, Yoo Jin; Lee, Seon-Yeong; Lee, So Won; Park, Jin Hyung; Han, Se Gyeong; Choi, Jeong Won; Park, Hyo-Jung; Cho, Mi-La; et al. (Frontiers in Immunology, 2025)
IntroductionSystemic sclerosis (SSc) is a chronic autoimmune disorder characterized by progressive fibrosis, vascular abnormalities, and immune dysregulation. Decreased expression of A20 (TNFAIP3), a key negative regulator of inflammation, has been shown to aggravate SSc pathogenesis by enhancing fibroblast activation and promoting collagen production. This study explores the therapeutic efficacy of A20 mRNA-lipid nanoparticle (LNP) delivery in restoring A20 expression and mitigating fibrosis through modulation of the TRAF6/NF-κB and Downstream Regulatory Element Antagonist Modulator (DREAM) -SMAD2 signaling pathways.MethodsHuman dermal fibroblasts were transfected with A20 mRNA -LNP and subsequently stimulated with transforming growth factor-beta (TGF-β). Protein expression levels and fibrotic markers were analyzed by Western blotting and quantitative PCR. In vivo, a bleomycin-induced mouse model of SSc received weekly intramuscular injections of A20 mRNA -LNP. The extent of fibrosis was assessed through histological analysis and immunohistochemistry.ResultsTransfection with A20 mRNA-LNP significantly suppressed TRAF6/NF-κB signaling and reduced fibrotic marker expression in vitro. In the SSc mouse model, A20 mRNA-LNP treatment markedly attenuated skin and lung fibrosis and decreased collagen deposition. Importantly, A20 overexpression led to downregulation of DREAM in vivo and inhibition of SMAD2 phosphorylation in vitro, indicating crosstalk between inflammatory and fibrotic pathways.DiscussionA20 mRNA therapy effectively alleviates fibrosis by restoring A20 expression and inhibiting TRAF6/NF-κB signaling, while also downregulating DREAM, a previously unrecognized target. This dual-pathway regulation underscores the role of A20 and DREAM as central modulators of fibrotic progression. These findings highlight the potential of A20 mRNA-LNP as a novel therapeutic strategy for SSc, offering a multifaceted approach that may surpass current treatment options by simultaneously targeting interconnected pathogenic pathways.